تحولات الخط العربي في العصر الرقمي: نماذج تعليمية وتطويرية: Transformasi Khat Arab Era Digital: Analisis Model Pendidikan dan Pengembangan - Hasbullah, Abdur Rouf; Makhisoh, Iis (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2025)
A variety of technological tools, digital media, and social media have streamlined learning, particularly for Tahsin al-Kitabah (improving writing) and Khat Araby (Arabic calligraphy). Online correction systems and diverse calligraphy applications like Kitabahku, Mashq, Ana Mukhtarifulkhat, and Kelk not only aid student learning but also stimulate their creativity. Consequently, educators must leverage these digital media as supportive learning tools. The